2023
DOI: 10.1136/bmjophth-2022-001202
|View full text |Cite
|
Sign up to set email alerts
|

Refractive error correction among urban and rural school children using two self-adjustable spectacles

Abstract: ObjectiveSelf-refracting spectacles (SRSs) have different optical and mechanical designs, which may affect the refractive outcome, depending on the experience of the end user. This study compared the performance of two SRS among children in Ghana.Methods and analysisA cross-sectional study of two Alvarez variable-focus SRS designs was conducted. A total of 167 children (mean age 13.6±1.6 years) identified as having refractive error were recruited from 2465 students who underwent screening. Subjects completed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
(80 reference statements)
1
4
2
Order By: Relevance
“…Compared with noncycloplegic autorefraction, we found self-refraction using fluid-filled design adjustable-focus spectacles to be noninferior and more hyperopic (mean difference, 0.32 D) among children aged 5 to 11 years. In contrast, a study among older children (12-17 years) in rural and urban Ghana using Alvarez design adjustable-focus spectacles found a significant myopic difference between self-refraction and noncycloplegic autorefraction (mean difference, −0.24 to −0.26 D) . We did not find a definitive association between the mean difference in refractive power between self-refraction and noncycloplegic autorefraction and either age or refractive power of cycloplegic refraction.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Compared with noncycloplegic autorefraction, we found self-refraction using fluid-filled design adjustable-focus spectacles to be noninferior and more hyperopic (mean difference, 0.32 D) among children aged 5 to 11 years. In contrast, a study among older children (12-17 years) in rural and urban Ghana using Alvarez design adjustable-focus spectacles found a significant myopic difference between self-refraction and noncycloplegic autorefraction (mean difference, −0.24 to −0.26 D) . We did not find a definitive association between the mean difference in refractive power between self-refraction and noncycloplegic autorefraction and either age or refractive power of cycloplegic refraction.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with previous self-refraction studies, we found a tendency toward greater myopic power, although no definitive difference, with self-refraction compared with cycloplegic refraction among children aged 5 to 11 years, likely due to noncycloplegic accommodation . The mean dioptric power inaccuracy reported in prior studies with older children (12-17 years) was −0.22 to −0.44 D, similar to what we observed among 5 to 11 year olds (−0.33 D) . We did not find a definitive association between difference in refractive power between self-refraction and cycloplegic refraction and age (ie, no increased tendency to overminus with younger age).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations